The effect of bending deformation on flexible electrodes during charging and discharging. (October 2021) - Shi, Yutao; Xu, Chengjun; Weng, Li; Wei, Yufeng; Chen, Bingbing; Wang, Yalei; Zhou, Jianqiu; Cai, Rui
Abstract: As the typical deformation mode, the bending deformation accompanies the entire useful life of flexible batteries. Due to the coupling of electrochemical processes, this bending behavior can severely damage flexible batteries. Herein, a complete physical model is developed to investigate the effect of bending deformation on flexible thin-film electrodes during the charge/discharge cycle. And the rate-dependent plastic flow in the electrode is modeled based on the evolution of the excess energy stored in the material. Two different bending forms of the flexible thin-film electrode are studied, and the stress and strain spectrums of the electrode during cyclic deformation are thoroughly discussed. The results show that the bending deformation has a significant effect on the evolution of the stress and strain of the electrode. Both constant bending deformation and cyclic bending deformation produce accumulated strain, but for entirely different reasons. The present work sheds light on the physical origin of strain accumulation for the flexible thin-film electrode and provides guidance for material design and the application of flexible batteries. Highlights: A complete physical model of the flexible electrode is developed. The charge/discharge-rate-dependent plastic deformation is discussed. Evolutions of plastic stress and strain during charge/discharge are studied. The viscoplastic finite element analysis confirms the theoretical results. Two different physical origins of strain accumulations are studied.